Visible light induced photoreduction of methyl orange by N-doped mesoporous titania - Joshi, Meenal M.; Labhsetwar, Nitin K.; Mangrulkar, Priti A.; Tijare, Saumitra N.; Kamble, Sanjay P.; Rayalu, Sadhana S. (Applied Catalysis A-General, 2009)
N-doped mesoporous titania was synthesized using templating method. Biopolymer chitosan was used as a template and also as a nitrogen source along with ammonium hydroxide. Three different types of N-doped mesoporous titania were synthesized by varying composition of chitosan and titania precursor. These photocatalysts were characterized using XRD, BET-SA, FTIR, UV-DRS, SEM-EDX and XPS analysis. The photocatalytic activity of mesoporous titania was studied by methyl orange (MO) photoreduction reaction. From the experimental results it was observed that the N-doped mesoporous titania (1:2) gives the highest photocatalytic reduction of MO as compared to N-doped mesoporous titania prepared with (1:1) and (1:3) stoichiometry. This could be due to the optimal level of `N' incorporation in the N-doped mesoporous titania (1:2). Photocatalysts reduce the MO dye into derivative of hydrazine. Photoactivity of N-doped mesoporous titania (1:2) is 1.0721 mg of MO reduced per g of TiO2 vis-a-vis 0.508 mg of MO reduced per g of TiO2 for Degussa P25 photocatalyst. The effect of various operating parameters like photocatalyst loading. initial concentration and intensity of light also has been studied. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: biopolymer; Chitosan; MO photoreduction; N-doped mesoporous titania; Visible active photocatalyst

Hydrogen evolution by a low cost photocatalyst: bauxite residue - Mangrulkar, Priti A.; Joshi, Meenal V.; Kamble, Sanjay P.; Labhsetwar, Nitin K.; Rayalu, Sadhana S. (International Journal of Hydrogen Energy, 2010)
Bauxite residue or red mud which is an aluminium industry waste has been used as a novel low cost photocatalyst active in visible light for the generation of hydrogen from water. The driving force behind the use of bauxite residue as a photocatalyst is not only the fact that it is widely available but also bauxite residue is a fine grained mixture of oxides and hydroxides (Fe(2)O(3), TiO(2), SiO(2), and Al(2)O(3), Al(OH)3). The photocatalyst was characterized with respect to BET-SA, UV-DRS, XRD, SEM and EDX. Hydrogen yield of 4600 mu mol/h/g of TiO(2) was achieved as compared to hydrogen evolution rate of 164 mu mol/h/g of TiO(2) for commercially available titania Degussa P-25. However, the hydrogen evolution was 20.85 mu mol/h/g of photocatalyst. The results suggest that bauxite residue appears to be a novel low cost photocatalyst. The various operating conditions of photocatalytic hydrogen generation were studied which include amount of catalyst, illumination intensity, illumination time, effect of various sacrificial donors etc. (C) 2009 Professor T. Nejat Veziroglu. Published by Elsevier Ltd. All rights reserved.
Keywords: Aluminium industry waste; Bauxite residue; Hydrogen generation; Red mud; Sacrificial donors

Photocatalytic degradation of phenolics by N-doped mesoporous titania under solar radiation - Mangrulkar, Priti A.; Kamble, Sanjay P.; Joshi, Meenal M.; Meshram, Jyotsna S.; Labhsetwar, Nitin K.; Rayalu, Sadhana S. (International Journal of Photoenergy, 2012)
In this study, nitrogen-doped mesoporous titania was synthesized by templating method using chitosan. This biopolymer chitosan plays the dual role of acting as a template (which imparts mesoporosity) and precursor for nitrogen. BET-SA, XRD, UV-DRS, SEM, and FTIR were used to characterize the photocatalyst. The doping of nitrogen into TiO2 lattice and its state was substantiated and measured by XPS. The photocatalytic activity of the prepared N-doped mesoporous titania for phenol and o-chlorophenol degradation was investigated under solar and artificial radiation. The rate of photocatalytic degradation was observed to be higher for o-chlorophenol than that of phenol. The photodegradation of o-chlorophenol was 98.62% and 72.2%, while in case of phenol, degradation to the tune of 69.25% and 30.58% was achieved in solar and artificial radiation. The effect of various operating parameters, namely, catalyst loading, pH, initial concentration and the effect of coexisting ions on the rate of photocatalytic degradation were studied in detail.